Description of two new huntsman spiders from Vietnam (Araneae, Sparassidae) - He Zhang; Quang Duy Hoang; Shuang Lei (ZooKeys)
Two new species of the sparassid genera Heteropoda Latreille, 1804 and Pseudopoda Jäger, 2000 are described from Vietnam: Heteropoda taygiangensis sp. nov. (♂) from Quang Nam Province and Pseudopoda tadungensis sp. nov. (♀) from Dak Nong Province. The new Pseudopoda species is described and diagnosed based on both morphological characteristics and DNA barcoding. DNA barcode data (COI) are provided for both new species.